Security of Tenure in Foreclosure Proceedings: The Judicial Role when Borrowers are Absent or Self-Represented - Lund, Anna (Ottawa Law Review / Revue de droit d’Ottawa, 2024)
The right to adequate housing requires that individuals not be evicted from their homes without being provided appropriate legal or other protections. In Canada, the federal government has promoted housing through mortgage-financed homeownership. Individuals risk losing their homes if they default on their mortgage. When an individual can no longer afford their mortgage payments, the law must reconcile the individual’s right not to be evicted without appropriate legal protections with a lender’s right to be paid. In a mortgage law system that prioritizes the economic interests of a lender, this is no easy task. This balance becomes especially difficult in court-based foreclosure proceedings because lenders are typically present and represented, and borrowers are frequently absent or self-represented.Through observing 105 residential foreclosure proceedings at the Edmonton Law Courts, this article explores the role of courts in preserving the integrity of the adversarial system and thereby promoting security of tenure. It examines how judges can adjust their role in the adversarial model to better protect self-represented and absent borrowers. It identifies nine strategies used by judges: scrutinizing the lender’s evidence, seeking additional information from the parties, scrutinizing the relief sought, raising new legal issues, enforcing consistency across cases, providing advice to borrowers, offering referrals to borrowers, encouraging negotiations, and assuming a problem-solving role. This article reveals that judges often assume an active role in an attempt to rectify the power imbalance in foreclosure proceedings. Furthermore, the mere presence of the borrower improves the judge’s ability to account for their interests in the proceedings and thereby safeguard their security of tenure.